2003
DOI: 10.1177/10883576030180040201
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents With Asperger Syndrome and Perceptions of Friendship

Abstract: This qualitative study investigated the perceptions of friendship faced by teenagers diagnosed With Asperger syndrome. This research aimed to provide teachers With an insight into the social World of Asperger syndrome from a student perspective. A multiple—case study approach Was used to collect data from 5 secondary school students in Australia. Data Were collected through the use of semistructured intervieWs. An inductive approach to data analysis resulted in a number of broad themes in the data: (a) underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 18 publications
5
103
0
1
Order By: Relevance
“…It has been suggested that preserved aspects of social performance in ASD may rely on compensatory mechanisms such as knowledge acquired through prior social learning and experience (Frith, 2004;Hill & Frith, 2003). This has been supported by recent qualitative work, in which participants with ASD reported that they often observe how others act in different situations (Carrington, Templeton, & Papinczak, 2003;Müller, Schuler, & Yates, 2008). …”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has been suggested that preserved aspects of social performance in ASD may rely on compensatory mechanisms such as knowledge acquired through prior social learning and experience (Frith, 2004;Hill & Frith, 2003). This has been supported by recent qualitative work, in which participants with ASD reported that they often observe how others act in different situations (Carrington, Templeton, & Papinczak, 2003;Müller, Schuler, & Yates, 2008). …”
Section: Introductionsupporting
confidence: 56%
“…This may be instrumental in helping people with ASD to extrapolate the rules underlying appropriate social conduct (Carrington et al, 2003;Müller et al, 2008), and teaching them how to circumvent their difficulties and find solutions to social problems (Bowler, 1992;Senju, 2012). Reliance on compensatory social knowledge may have aided those with ASD with awkwardness ratings and rank-ordering, both of which are less demanding than generating free verbal responses.…”
Section: Social Models Of Asdmentioning
confidence: 99%
“…Instead, they reported that their students had a desire to fit in. Previous research has also noted this desire to belong (Daniel & Billingsley, 2010), with one study reporting that autistic adolescents used masquerading to fit in with their peers (Carrington et al, 2003b). It is possible that these adolescents do have some motivation to fit in with their peers, but they do not wish to do so by conforming.…”
Section: Discussionmentioning
confidence: 98%
“…As Milton (2013) notes, although the social experiences of autistic individuals are different to that of typical individuals, there is not necessarily a lack of interest in, or motivation for, social experiences, as is often assumed. For example, Carrington et al (2003b) found that adolescents with autism reported using "masquerading" -pretending to know how social situations work -to hide their social difficulties from typical peers. Thus, it is plausible that autistic individuals would be to some degree concerned about what others think of them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation